PENGARUH PENERAPAN MODEL PEMBELAJARANwKOOPERATIF TIPE STAD (STUDENT TEAMS-ACHIAVEMENT0DIVISIONS)oDAN PENGETAHUAN AWAL TERHADAPPHASILoBELAJAR SENI RUPA PADA SISWAnKELASkVII DI SMPNk2 TANJUNG EMAS TANAH DATAR - KHAIRUNISSA SUKARDI, Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2019)
Thecpurposedof thisvjournal is to find out the increase in learning outcomes of class VII students of SMP 2 Tanjung Emas Tanah Datar through the applicationmof theccooperativexlearning model type STAD (Student Teams-AchievementvDivisions) and initial knowledge. The research was conducted on 1 March until 1 April 2019. This study was a quantitative research type experimental pre-test post-test. The technique used is observation and testing. The difference in increasing student understanding was analyzed by the t test. Based on the results of the study showed an increase in the average score of the post-test. The post-testnresults were 0,000 with a significance level of 0.05. Then it can be concludedmthat there is an increase in the learningvoutcomes of0class VII students of junior high school 2 tanjung emas flat land using the cooperative learning modelkstad type (studentlteams-achievementwdivisions) and initial knowledge.keywords: lSTAD (StudentwTeams-Achievement Divisions),llearning outcomes